2003
DOI: 10.32609/0042-8736-2003-8-4-30
|View full text |Cite
|
Sign up to set email alerts
|

Structural Maneuver and Economic Growth

Abstract: The article proposes the realization of structural reforms in the Russian economy. The author points out three sectors of the modern economy: the export sector, mainly energy and raw materials; the sector oriented at domestic market; the non-market sector, which includes, besides budgetary sphere, electricity production, gas industry and utilities. The idea is to considerably limit the size of the non-market sector at the expense of the said industries and broaden in them the sphere of competitive relations, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The influence of culture on economic development has been actively studying. Thus, a group of Russian researchers concluded that Russian culture holds back the country's economic development [1,2,3,4]. These works are supported by some empirical data [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The influence of culture on economic development has been actively studying. Thus, a group of Russian researchers concluded that Russian culture holds back the country's economic development [1,2,3,4]. These works are supported by some empirical data [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 90%
“…Studies of social and economic processes in Spain and the countries of the Spanish world were carried out in works [1,22,23,24].…”
Section: Introductionmentioning
confidence: 99%